Robust Association Tests for the Replication of Genome-Wide Association Studies. - Joo, Jungnam; Park, Ju-Hyun; Lee, Bora; Park, Boram; Kim, Sohee; Yoon, Kyong-Ah; Lee, Jin Soo; Geller, Nancy L. (BioMed Research International, 2015)
In genome-wide association study (GWAS), robust genetic association tests such as maximum of three CATTs (MAX3), each corresponding to recessive, additive, and dominant genetic models, the minimum p value of Pearson’s Chi-square test with 2 degrees of freedom, and CATT based on additive genetic model (MIN2), genetic model selection (GMS), and genetic model exclusion (GME) methods have been shown to provide better power performance under wide range of underlying genetic models. In this paper, we demonstrate how these robust tests can be applied to the replication study of GWAS and how the overall statistical significance can be evaluated using the combined test formed by p values of the discovery and replication studies.